Transcriptome analysis of the gene expression of M. iliotibialis lateralis affected by dietary methionine restriction - Li, Desheng; Chen, Fei; Tian, Yumin; Su, Yuhong (Frontiers in Physiology, 2023)
Methionine (Met) is an important amino acid related to the development of skeletal muscle. This study investigated the effects of dietary Met restriction on the gene expression of M. iliotibialis lateralis. A total of 84 day-old broiler chicks (Zhuanghe Dagu) with a similar initial body weight (207.62±8.54g) were used in this study. All birds were divided into two groups (CON; L-Met) based on the initial body weight. Each group had 6 replicates with 7 birds per replicate. The experimental period was 63 days (phase 1, days 1-21; phase 2, days 22-63). According to the nutritional requirements of Zhuanghe Dagu chickens, we provided a basal diet (0.39% Met levels during phase 1 and 0.35% Met levels during phase 2, as fed-basis) to the birds in CON group, while provided a Met-restricted diet (0.31% Met levels during phase 1 and 0.28% Met levels during phase 2, as fed-basis) to the birds in L-Met group. Growth performance of broiler chicks and their M. iliotibialis lateralis development parameters were measured on day 21 and 63. In this study, dietary Met restriction did not affect the growth performance of broiler chicks but hindered the development of M. iliotibialis lateralis on both sampling timepoints. On the final day, three birds selected from each group (3 from CON and 3 from L-Met) were used to obtain M. iliotibialis lateralis from leg muscle for further transcriptome analysis. Transcriptome analysis revealed that dietary Met restriction significantly upregulated 247 differentially expressed genes (DEGs) and downregulated 173 DEGs. Additionally, DEGs were mainly enriched in 10 pathways. Among DEGs, we observed that dietary Met restriction downregulated the expression of CSRP3, KY, FHL1, LMCD1, and MYOZ2 in M. iliotibialis lateralis. Therefore, we considered that dietary Met restriction had negative effects on the development of M. iliotibialis lateralis, genes of CSRP3, KY, FHL1, LMCD1, and MYOZ2 may serve as potential functional genes involved in this process.